Bodily Integrity and the Politics of Circumcision Culture, Controversy, and Change - Denniston, George C.; Grassivaro Gallo, Pia; Hodges, Frederick M.; Milos, Marilyn Fayre; Viviani, Franco (Springer Netherlands : Imprint: Springer, 2006)
Circumcision is a cultural phenomenon that affects 15.3 million children and young adults annually. In terms of gender, 13.3 millions boys and 2 million girls are subjected to the involuntary removal of part or all of their external sex organs every year. Few people, however, ask why such practices persist or how modern societies can tolerate this inherent violation of human rights. The problem of female circumcision is being addressed on an international level, while male circumcision remains a subject many academics are reluctant to fully or impartially examine. This book explores the problem of male and female circumcision in modern society from religious, anthropological, psychological, medical, legal, and ethical perspectives. Bodily Integrity and the Politics of Circumcision: Culture, Controversy, and Change illuminates the vulnerability of human society to medical, economic, and historical pressures. It provides a much-needed, thoughtful, and detailed analysis of the devastating impact of circumcision on bodily integrity and human rights, and it provides hope for change.